2019
DOI: 10.3389/fpsyg.2019.00045
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Academic Self-Efficacy and Study Progress Among College Students – The SHoT Study, Norway

Abstract: Student life can be stressful and for some students it may cause mental distress. Besides being a major public health challenge, mental distress can influence academic achievement. The main objectives of the current study were to examine associations of mental distress with academic self-efficacy and study progress. A secondary aim was to examine mental health help seeking for students with mental distress. Data was derived from the Norwegian Students’ health and welfare survey 2014 (SHOT 2014) which is the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
133
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(158 citation statements)
references
References 53 publications
10
133
1
14
Order By: Relevance
“…The impairment of psychological well-being has been found to progress with the advancing years at school [46]. The study of Grøtan et al reported a strong association of mental distress with poorer academic self-efficacy as well as with slower study progress [47]. The presence of depression may increase smoking rate in youth indirectly by increasing their vulnerability and acceptance of peer norms [5].…”
Section: Discussionmentioning
confidence: 99%
“…The impairment of psychological well-being has been found to progress with the advancing years at school [46]. The study of Grøtan et al reported a strong association of mental distress with poorer academic self-efficacy as well as with slower study progress [47]. The presence of depression may increase smoking rate in youth indirectly by increasing their vulnerability and acceptance of peer norms [5].…”
Section: Discussionmentioning
confidence: 99%
“…It also suggests that EC and ER will be negatively related to stress, since they are resources that facilitate the use of more functional strategies by improving the management of stress (Bryant and Malone, 2015;Perera and DiGiacomo, 2015;Schönfeld et al, 2016;Zeidner and Matthews, 2016) (hypothesis 1). Similarly, as discussed above, given that selfefficacy appears to affect the individual's self-perceived ability to cope with stress and her assessment of the resources available to her (Soysa and Wilcomb, 2015;Valle et al, 2015;Grøtan et al, 2019), it is expected that self-efficacy will be negatively related to the levels of perceived stress (hypothesis 2).…”
Section: Introductionmentioning
confidence: 91%
“…The evidence suggests that high levels of self-efficacy are associated with low levels of perceived stress (Karademas and Kalantzi-Azizi, 2004;Zhao et al, 2015;Dominguez-Lara, 2018). In consonance with this, low levels of efficacy expectations are related with high levels of anxiety and stress (Soysa and Wilcomb, 2015;Valle et al, 2015;Grøtan et al, 2019). The reason for these associations is the role of expectations as protective or buffering factors against stress (Frick et al, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…Devoting time to activities apart from studies-be it a job, social or political engagement or pursuit of a hobbyhave proven to affect study progress [36]. Delays in study progress, however, have been found to be linked to mental distress [37]. At the organisational (university) level, interruptions ultimately pose perils; accumulating interruptions or transfers may create additional teaching and administrative costs.…”
Section: Discussionmentioning
confidence: 99%